Chronostratigraphic framework and depositional environments in the organic‐rich, mudstone‐dominated Eagle Ford Group, Texas, USA. Issue 5 (22nd February 2018) - Minisini, Daniel; Eldrett, James; Bergman, Steven C.; Forkner, Rob
Abstract: Since the beginning of the century, several authors have hypothesized and documented the presence of bottom currents during the deposition of mudstones, including mudstones rich in organic matter, challenging the assumption that persistent low‐energy conditions are necessary prerequisites for deposition of such sediments. More processes responsible for transport and deposition of mudstones mean also more processes acting contemporaneously in different parts of a basin. Without a precise and robust chronostratigraphic framework, however, it is not possible to characterize these differences. The new data reported here provide a profoundly different understanding of the controls on sedimentation in distal continental shelf platforms. To enhance the understanding of the different coeval environments of deposition coexisting in a muddy system, the Upper Cretaceous Eagle Ford Group, deposited on the Comanche carbonate platform, has been investigated by integrating sedimentology, mineralogy, geochemistry and palaeoecology, and creating age models in different physiographic sectors using biostratigraphy and geochronology. Data from two cores and 41 outcrops were analysed with a telescopic approach, from grain scale to basin scale. Nine temporal stages over a ca 8 Myr interval ( ca 98 to 90 Ma) were defined in an area that spans 75 000 km 2 . Finally, the different environments of deposition recorded within each of the nine stages were interpreted. The construction of the chronostratigraphic framework also allowed: measuring the duration of a basin‐wide gradational increase in energy in the water column ( ca 1 Myr) and a hiatus confined into the shallower water sector ( ca 2 Myr); determining the mean eruption frequency of volcanoes ( ca 9 kyr); and the time of inundation of the Western Interior Seaway (97·5 to 97·1 Ma). The context, the outcrops–cores–logs correlations, the large data set (Appendix S1 ), the high‐precision and well‐calibrated constraints represent an unprecedented contribution for future regional facies models of organic‐rich units and for improvements of key aspects in the industry of unconventional resources.